Distribución espacial vertical de las partículas en suspensión PM10 del medio atmosférico urbano en Segunda Jerusalén-Rioja-San Martín-Perú - Herrera Díaz, Santos Clemente (2011)
This document contains the final report of the thesis entitled: "SPATIAL VERTICAL DISTRIBUTION OF THE PARTICLES IN SUSPENSION PM10 OF THE ATMOSPHERIC URBAN WAY IN THE SECOND JERUSALEN-RIOJA-SAN MARTIN-PERU", to obtain the Academic degree of Master in environmental management. Second Jerusalem is a population located in Elias Soplin Vargas district, in the Rioja province, San Martin region. Its population is approximately 6.412 inhabitants, and in the entire field of district are 10.427 inhabitants, whose main economic activity is referring to agriculture. This population has the particularity to host a cement production plant, as well as the quarry extracted the raw material for that industry. This situation has sensitized the population cope with the problem of environmental pollution generated by the cement industry and has been confronted with the Cementos Selva S. A company, responsible for the plant. The central objective of the study has been the determination of the particulate material in suspension in the atmospheric environment of the Segunda Jerusalen population. By way of secondary objective was raised the assessment of the potential environmental impacts of particulate matter in suspension and the approach of control measures, mitigation and prevention of air pollution, produced by the particulate material PM10. To achieve the aims there was effected a program of air monitoring in two stages and having in consideration the stations of the year. The first stage (winter vi epoch), it was realized from April 25 to May 02, 2009 and the second stage (summer epoch) fulfilled from 12 to 19 of September of the same year, In both cases used a sampling equipment automatic and it is determined the quantity of particles in suspension of size equal to or less than 10 μm (PM10). Then, we evaluated the potential environmental impacts by applying matrix methods, (Adapted from Canter L, 1998). The study concludes, indicating that the quality of the air of the atmospheric environment in Second Jerusalem population, with regard to particulate material in suspension concerning particles PM10, meets the standards peruvian law, but it is confirmed the presence of this material in averages whose quantities are 10.14 μg/m3 for the time of winter and 13.37 μg/m3 for the time of summer, appearing higher concentrations. The (D. S N° 074-2001-PCM), mentions that the maximum allowable limits (PML), for particulate material PM10, correspond to concentrations of 150 ug/m3. With regard to the direction of the wind influences in a manner not very favorable to the present study for both times of summer and winter, the trends in most frequently recorded are orientated to the NNW, ENE, ESE, E and relatively to the North, given that the Cementos Selva S.A. plant, located in the South of the population of Second Jerusalem.